2022
DOI: 10.1088/2515-7647/acadc1
|View full text |Cite
|
Sign up to set email alerts
|

Joint time-frequency analysis on space-time-coding digital metasurfaces

Abstract: Space-time and time-varying metastructures have attracted a lot of research interest in recent years. On the other hand, digital programmable metasurfaces have also gained great attention owing to their powerful capabilities in controlling electromagnetic (EM) fields and waves in real time, which is very suitable for implementing spatiotemporal modulations in a digital manner. Accordingly, space-time-coding (STC) digital metasurfaces have recently been proposed to realize advanced manipulations of EM wavefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…By controlling the variation of characterization parameters of metasurfaces in the spatial and time domains, many novel physical phenomena that traditional space-modulated metasurfaces cannot achieve have emerged. Due to the introduction of time-varying parameter manipulation, time modulation of metasurfaces greatly expands their application range [142,143,[163][164][165][166].…”
Section: Time-modulated Metasurfacesmentioning
confidence: 99%
“…By controlling the variation of characterization parameters of metasurfaces in the spatial and time domains, many novel physical phenomena that traditional space-modulated metasurfaces cannot achieve have emerged. Due to the introduction of time-varying parameter manipulation, time modulation of metasurfaces greatly expands their application range [142,143,[163][164][165][166].…”
Section: Time-modulated Metasurfacesmentioning
confidence: 99%
“…This approach introduces an extra dimension of control -time -leading to unparalleled capabilities in wave manipulation and the discovery of intriguing physical phenomena and applications. [26][27][28][29][30][31][32][33][34] In 2018, we put forward the concept of space-time-coding (STC) digital metasurfaces, building upon the digital programmable metasurface platform. [35] By dynamically switching the elements' constitutive parameters (e.g., amplitudes and/or phases) in both space and time, we demonstrated that STC digital metasurfaces can simultaneously manipulate waves and information in spatial and frequency domains.…”
Section: Introductionmentioning
confidence: 99%